The Influence of the STEM Approach on Elementary School Students' Higher-Order Thinking Skills (HOTS) - Karin Riska Puspitasari; Tabroni Tabroni; Fia Alifah Putri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to examine and analyze the effectiveness of the Science, Technology, Engineering, and Mathematics (STEM) approach on improving students' Higher Order Thinking Skills (HOTS) in IPAS subjects. The method used was a quasi-experimental design with a non-equivalent control group design involving 32 fifth-grade students at MIS Kurnia Kota Jambi, who were divided into experimental and control groups. Data were collected through HOTS test instruments and analyzed using the Independent Sample T-Test. The results showed that there was a significant difference in students' higher-order thinking skills, with the experimental class obtaining a post-test average score of 73.31, which was much higher than the control class, which only achieved 50.44. In conclusion, the integration of systematic STEM steps (observation, new ideas, innovation, creation, and social values) effectively transformed students' cognition from a low level to a level of analysis, evaluation, and creation. This approach has been proven to be able to bridge the understanding of abstract scientific theory into concrete solutions, making it highly relevant for developing the adaptive competencies of elementary school students in the modern era.